Generosity Behaviours of Nursing Students in Caring for Critically ill Patients, Boromarajonani College of Nursing Udon Thani - Kitkhaundee, Benjawan; Khoyun, Siriorn; Lomon , Jutharat; Thoin , Pasinee; Srioad , Phattnee (Medical Journal of Sakon Nakhon Hospital, 2024)
This study aimed to examine generosity behaviors in caring for critically ill patients among nursing students through self-assessment and supervising instructor evaluation. The sample consisted of 147 third-year nursing students in the academic year 2023 at Boromarajonani College of Nursing Udon Thani and 10 supervising instructors. The research instrument was a 5-point rating scale questionnaire assessing generosity behaviors in critical care nursing, with an Item-Objective Congruence Index (IOC) of 0.67-1.00. The Cronbach's alpha reliability coefficients for student self-assessment and supervisor evaluation forms were 0.96 and 0.97, respectively. Data were analyzed using descriptive statistics including mean and standard deviation, and differences were compared using an independent t-test. The study found that both nursing students' self-assessment and supervising instructors' evaluation of generosity behaviors in caring for critically ill patients were at high levels across all aspects, with morality and ethics receiving the highest mean scores. Overall, there was no significant difference between students' self-assessment and supervising instructors' evaluation (t = 1.80, p = 0.07). However, when comparing individual aspects, students rated themselves significantly higher than their supervising instructors in three areas: ability, confidence building, and commitment (p < 0.01). These findings can be applied to improve the curriculum design in nursing practice courses to comprehensively develop students' generosity behaviors in patient care.